Konsep Diri, Dukungan Sosial dan Penyesuaian Sosial Mahasiswa Pendatang Di Bali - Gunarta, Meding Edie (Persona:Jurnal Psikologi Indonesia, 2015)
Abstrac. The purpose of this study to tes the relationship between self concept and socialsupport for social adjustment in student from outside at IKIP PGRI Bali. The variable of thestudy are measured by using self concept, social support and social adjustment. The inputdata is analyzing by using regression t-test. The result show that self concept and socialsupport does have relation with social adjustment, where are F = 11,277 and p = 0,000(p<0,001). Retrived RÂ² = 0,264 means of social adjustment student from outside explainedby variable self concept and social support. The result of the t test analysis showed nodifference adjustment, self concept and social support among male student and femalestudents.Keywords : Selt concept, Social support, Social adjustment